Determining Criteria and Their Weights for Evaluating the Capability of Gen-Z Human Resources Meeting Japanese Labour Market Expectations A Case Study in Binh Dinh - Chuong M. Tran; Thang Q. Dao; Linh P.V. Dao; Kim M. Le (My University, 2021)
Determining Criteria and Their Weights for Evaluating the Capability of Gen-Z Human Resources Meeting Japanese Labour Market Expectations A Case Study in Binh Dinh
Keywords: Gen-Z Capability; Evaluation weights; Japanese market